Magnetic Non-invasive Auricular Acupuncture During Eye-Exam for Retinopathy of Prematurity in Preterm Infants: A Multicentre Randomized Controlled Trial - Gan, Kimberly M. L.; Oei, Ju-Lee; Quah-Smith, Im; Kamar, Azanna A.; Lordudass, Alexis A. D.; Liem, Kian D.; Lindrea, Kwee Bee; Daly, Mary; Gaunker, Nilima; Mangat, Avneet K.; Yaskina, Maryna; Schmölzer, Georg M. (Frontiers in Pediatrics, 2020)
Background Eye exam for Retinopathy of prematurity (ROP) is a painful procedure and pharmacological analgesia might be ineffective. We hypothesized that magnetic auricular acupuncture (MAA) compared to placebo will decreasing pain during ROP exam in preterm infants. Methods Multicentre randomized controlled trial conducted in three hospitals (Australia, Canada, and Malaysia). Eligibility: >32 weeks, ROP exam, not sedated, and parental consent. A total of 100 infants were randomized (1:1) to MAA (n=50) or placebo (n=50). MAA stickers or placebo were placed on both ears by an unblinded investigator. Pain was assessed using the Premature Infant Pain Profile. Primary analyses were by intention-to-treat. ClinicalTrials.gov:NCT03650621 Findings The mean (standard deviation, SD) gestation, birthweight, and postnatal age were (MAA 28(3) vs. placebo 28(2)weeks; MAA 1,057(455) vs. placebo 952(273)g; MAA 7(3) vs. placebo 7(3)weeks. Placebo infants had significantly higher PIPP scores during (mean difference 1.6 points (95%CI 0.1-3.1) and one hour (mean difference 1.5 points (95%CI 0.7-2.2) after the procedure (p<0.03). Heart rate was lower (173(22) vs. 184(18)/min) and oxygen saturations were higher (93.8(6.2) versus 91.7(6.1)%, p=0.05) in MAA infants. No adverse effects. Interpretation MAA may reduce physiological pain responses during and after ROP exam in preterm infants. Assessment of long-term effects are warranted.